COVID-19-Associated Rhinocerebral Mucormycosis, an Incidental Finding or a Matter of Concern – Mixed-Method Systematic Review - Andreescu M; Moldovan C; Lespezeanu DA; Mocanu AI; Schipor MA; Mocanu H (Infection and Drug Resistance, 2024)
Mihaela Andreescu,1,2,* Cosmin Moldovan,3,4,* Delia-Andreea Lespezeanu,5,6,* Adela-Ioana Mocanu,5,7 Mihai-Adrian Schipor,8 Horia Mocanu9,10,* 1Department of Hematology, Faculty of Medicine, “Titu Maiorescu” University, Bucharest, 031593, Romania; 2Department of Hematology, Colentina Clinical Hospital, Bucharest, 01171, Romania; 3Department of Medical Surgical Disciplines, Faculty of Medicine, “Titu Maiorescu” University, Bucharest, 031593, Romania; 4Department of General Surgery, Witting Clinical Hospital, Bucharest, 010243, Romania; 5Doctoral School, Faculty of Medicine, “Titu Maiorescu” University, Bucharest, 031593, Romania; 6“Ion Pavel” Diabetes Center, National Institute of Diabetes, Nutrition and Metabolic Diseases “Prof.Dr.N.C. Paulescu”, Bucharest, 030167, Romania; 7Department of ENT&HNS, Polimed Medical Center, Bucharest, 040067, Romania; 8Institute of Space Technology and Space Applications, University of the Bundeswehr, München, 85579, Germany; 9Department of ENT&HNS, Faculty of Medicine, “Titu Maiorescu” University, Bucharest, 031593, Romania; 10Department of ENT&HNS, Găești City Hospital, Găești, Dâmbovița, 135200, Romania*These authors contributed equally to this workCorrespondence: Adela-Ioana Mocanu, Polimed Medical Center, Bloc 67, Calea Văcărești 280, Bucharest, 040063, Romania, Tel +40723400435, Email adela.ioana.mocanu@gmail.com Mihaela Andreescu, Faculty of Medicine, “Titu Maiorescu” University, Str. Gheorghe Petrașcu 67A, Bucharest, 031593, Romania, Tel +40744559730, Email tevetmihaela@gmail.comAbstract: With the advent of COVID-19, the number of patients diagnosed with mucormycosis has increased, especially in developing countries. The reason behind this increase is that COVID-19 causes hypoxia that promotes the growth of fungus. To identify the association between mucormycosis and COVID-19, in critically ill or immunocompromised COVID-19 patients. The literature included in the review was researched from October 1, 2021, to November 1, 2022, by using the Google Scholar database as the search engine. Of the 20 articles included, there were 4 case reports, 2 case series, 10 narrative reviews, and 4 quantitative studies. Mucormycetes growth is caused by several factors, including hyperglycemia owing to previously existing diabetes or excessive use of steroids, increased ferritin levels owing to the inflammatory cascade initiated by COVID-19, and immunosuppression caused by the use of steroids or other immunosuppressive therapy. Reduced white-cell count and activity in COVID-19 leads to increased germination of fungal spores hence developing a catastrophic picture of rhinocerebral mucormycosis. Considering that the hematological patient is frequently treated with cortisone, immunosuppressed due to the underlying condition, but also through the administered therapy, the association with a possible diabetes makes this patient susceptible to developing rhinocerebral mucormycosis during COVID-19 infection. Despite being severe, the association between mucormycosis and COVID-19 is specific and treatable. Development of mucormycosis in hematological patients suffering from severe COVID-19 disease is dangerous, yet not compulsory and can be prevented. Using a common steroid-dose protocol with hyperbaric oxygen and necessary preventive measure reveals the disease as a superadded infection. Hypoxia, poor glycemic control and overuse of steroids or immunosuppressive drugs cause it.Keywords: COVID-19-associated mucormycosis, immunocompromised, critical, COVID-19, mucormycosis, fungal infection